Is basal ultrasensitive measurement of calcitonin capable of substituting for the pentagastrin‐stimulation test?. (25th January 2013) - Pina, Géraldine; Dubois, Séverine; Murat, Arnaud; Berger, Nicole; Niccoli, Patricia; Peix, Jean‐Louis; Cohen, Régis; Guillausseau, Claudine; Charrie, Anne; Chabre, Olivier; Cornu, Catherine; Borson‐Chazot, Françoise; et al.
Summary Objective To evaluate a second‐generation assay for basal serum calcitonin (CT) measurements compared with the pentagastrin‐stimulation test for the diagnosis of inherited medullary thyroid carcinoma (MTC) and the follow‐up of patients with MTC after surgery. Recent American Thyroid Association recommendations suggest the use of basal CT alone to diagnose and assess follow‐up of MTC as the pentagastrin (Pg) test is unavailable in many countries. Design Multicentric prospective study. Patients A total of 162 patients with basal CT <10 ng/l were included: 54 asymptomatic patients harboured noncysteine 'rearranged during transfection' (RET) proto‐oncogene mutations and 108 patients had entered follow‐up of MTC after surgery. Measurement All patients underwent basal and Pg‐stimulated CT measurements using a second‐generation assay with 5‐ng/l functional sensitivity. Results Ninety‐five per cent of patients with basal CT ≥5 ng/l and 25% of patients with basal CT <5 ng/l had a positive Pg‐stimulation test (Pg CT >10 ng/l). Compared with the reference Pg test, basal CT ≥5 ng/l had 99% specificity, a 95%‐positive predictive value but only 35% sensitivity (P < 0·0001). Overall, there were 31% less false‐negative results using a 5‐ng/l threshold for basal CT instead of the previously used 10‐ng/l threshold. Conclusion The ultrasensitive CT assay reduces the false‐negative rate of basal CT measurements when diagnosing familial MTC and in postoperative follow‐up compared with previously used assays. However, its sensitivity to detect C‐cell disease remains lower than that of the Pg‐stimulation test.